2004
DOI: 10.1016/j.eneco.2004.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Technological learning for carbon capture and sequestration technologies

Abstract: This paper analyzes potentials of carbon capture and sequestration technologies (CCT) in a set of long-term energy-economic-environmental scenarios based on alternative assumptions for technological progress of CCT. In order to get a reasonable guide to future technological progress in managing CO 2 emissions, we review past experience in controlling sulfur dioxide (SO 2 ) emissions from power plants. By doing so, we quantify a ''learning curve'' for CCT, which describes the relationship between the improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(73 citation statements)
references
References 21 publications
3
70
0
Order By: Relevance
“…This formulation of a learning curve, first proposed by Wright (1936) to describe productivity improvements in the manufacture of an aircraft, has been widely adopted in the literature and in advanced energy-economic models to describe cost reductions as a function of cumulative production or deployment of a technology (Boston Consulting Group, 1968;Argote and Epple, 1990;McDonald and Schrattenholzer, 2001;Rubin et al, 2004;Riahi et al, 2004). The quantity 2…”
Section: àBmentioning
confidence: 99%
“…This formulation of a learning curve, first proposed by Wright (1936) to describe productivity improvements in the manufacture of an aircraft, has been widely adopted in the literature and in advanced energy-economic models to describe cost reductions as a function of cumulative production or deployment of a technology (Boston Consulting Group, 1968;Argote and Epple, 1990;McDonald and Schrattenholzer, 2001;Rubin et al, 2004;Riahi et al, 2004). The quantity 2…”
Section: àBmentioning
confidence: 99%
“…However, in this analysis, learning is limited only for some specific technologies for the simplicity of the calculation. Riahi et al [57] incorporated the learning curve into the energy-modeling framework MESSAGE-MACRO to analyze market potentials of carbon capture and sequestration technologies. They concluded that endogenized technological learning is computationally infeasible for their model, which included over 400 energy technologies and operate on 11 world regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While policies of carbon sequestration technologies are currently being discussed and tested (for example Herzog, 2001;Riahi, Rubin, Taylor, Schrattenholzer, & Hounshell, 2004), it may be worthwhile to further evaluate land use policies favoring both maintenance and re-growth of temperate forest systems. Not only may forest re-growth policies serve (in the aggregate) as substantial and continual carbon sinks, but they also provide additional direct, indirect, and non-use values that are of interest to society (Plantinga & Wu, 2003).…”
Section: Resultsmentioning
confidence: 99%